EPISTEMOLOGI INTEGRATIF: SINTESIS RASIONALISME, EMPIRISME, REALISME, DAN TASAWUF DALAM MEMBANGUN PARADIGMA ILMU PENGETAHUAN MODERN - Dipalpa Rego; Efendi Efendi; Muhammad Zalnur (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This article discusses Integrative Epistemology: the synthesis of rationalism, empiricism, realism, and Sufism in constructing a modern scientific paradigm as an effort to build a holistic and transformative framework of knowledge amid the reductionist crisis of modern science. The main objective of this study is to formulate an integrative epistemological model that unites the strengths of rationality, empirical experience, objective reality, and spiritual consciousness into a coherent system of knowledge. This research employs a qualitative approach based on library research by examining relevant classical and contemporary literature in the fields of philosophy of science and Islamic thought. The results of the analysis indicate that rationalism provides a deductive-logical foundation for the structure of science, empiricism offers an objective verification mechanism through sensory experience, while realism maintains the relationship between knowledge and external reality. These three are perfected by the epistemology of Sufism, which places qalb (the heart) and ma‘rifah (intuitive knowledge) as the transcendental dimensions of knowledge. The integration of these four epistemological perspectives produces an integralistic scientific paradigm that not only explains phenomena rationally and empirically but also embeds ethical, spiritual, and ontological values. Thus, integrative epistemology serves as a conceptual alternative for the renewal of modern science so that knowledge is not only methodologically true but also theologically and existentially meaningful